Beyond Communicative Competence: Integration Of Intercultural Communicative Competence in Primary ESL Classroom - Siaw, Jun Ning; Megawati Soekarno (PPIB, UMS, 2024)
In recent years, intercultural communicative competence (ICC) has become one of the goals of English language teaching in several countries in view of its emphasis on developing learners’ ability to communicate with people from various cultural backgrounds. In Malaysia, the implementation of CEFR-aligned curriculum has brought about the introduction of imported textbooks. Delving into the primary ESL classroom context, this study aimed to investigate the components of ICC in Get Smart Plus 4 and explore activities that contribute to learners’ ICC development. A content analysis was carried out to analyse the content of the textbook based on the listed components of intercultural competence. The findings revealed that Get Smart Plus 4 contained activities that contribute to the development of learners’ intercultural knowledge, attitudes, and skills. This study suggests that utilising the content in the imported textbooks is beneficial in promoting learners’ ICC in the primary ESL classroom.